What can science do in the face of pandemics? - Alexander Bogner (Culture, Practice & Europeanization)
In 2020, the Austrian Academy of Sciences (ÖAW) publicly announced a prize question: “What can science do in the face of pandemics?” (2021). For this journal article the prize-winning essay submitted by the author was translated, updated and - thanks to helpful reviewer comments - revised. Science, it is argued, has different roles in times of crisis: First of all, it must educate about the (changing) crisis situation and provide as robust data, studies and facts as possible. In order to stabilize public trust in science, it is also necessary to provide the public an insight into the logic of scientific knowledge production and related uncertainties and insufficiencies. Last but not least, science has to educate about the limits of its own responsibility and authority. This means that the basic difference between science and politics should not be blurred. Especially in times of crisis, when the political value of science is particularly evident, science should avoid the impression that it can replace political decision-making thanks to its findings.